1994
DOI: 10.1002/mc.2940090103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of two separate mechanisms for the decrease in aryl sulfotransferase activity in rat liver during early stages of 2‐acetylaminofluorene–induced hepatocarcinogenesis

Abstract: Enzymatic and immunohistochemical experiments were conducted to evaluate the mechanistic basis for the downregulation of the important detoxication/bioactivation enzyme aryl sulfotransferase IV (AST IV) during 2-acetylaminofluorene (2AAF)-induced hepatocarcinogenesis. To distinguish between possible genotoxic and cytotoxic actions of 2AAF, three different dietary protocols were used in these experiments: group 1 received 2AAF for 12 wk, group 2 received 2AAF for 3 or 6 wk and then a control diet lacking xenobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Our present data indicate that resistance of preneoplastic GST7-7 ϩ hepatocytes towards growth inhibitory effects of 2-AAF may not be the consequence of their decreased bioactivation of this compound but rather be caused by failure to express nuclear p53. The decrease in sulfotransferase activity responsible for bioactivation of the 2-AAF metabolite N-OH-AAF in these cells during 2-AAF-induced hepatocarcinogenesis 48 may instead be secondary to the lack of p53-mediated growth arrest, as we have shown previously that N-OH-AAF sulfotransferase activity is down-regulated during the cell cycle. 49 In conclusion, we have found that the lack of nuclear p53 in focal hepatocytes might be related to nuclear exclusion of p53 by Mdm2 and/or Bcl-2.…”
Section: Discussionmentioning
confidence: 62%
“…Our present data indicate that resistance of preneoplastic GST7-7 ϩ hepatocytes towards growth inhibitory effects of 2-AAF may not be the consequence of their decreased bioactivation of this compound but rather be caused by failure to express nuclear p53. The decrease in sulfotransferase activity responsible for bioactivation of the 2-AAF metabolite N-OH-AAF in these cells during 2-AAF-induced hepatocarcinogenesis 48 may instead be secondary to the lack of p53-mediated growth arrest, as we have shown previously that N-OH-AAF sulfotransferase activity is down-regulated during the cell cycle. 49 In conclusion, we have found that the lack of nuclear p53 in focal hepatocytes might be related to nuclear exclusion of p53 by Mdm2 and/or Bcl-2.…”
Section: Discussionmentioning
confidence: 62%